Innovative Technologies as a Development Factor of Primary Class Students on the Base of Information Science (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article describes various methods of teaching computer science and its specific features in elementary grades. Methodological recommendations on the use of innovative technologies in the teaching of computer science in the primary classes of general education schools are presented. It is proposed to improve the quality of lessons with the help of innovative technologies.